The Gift in the English Law/ An Analytical Comparative Study with the Iraqi Civil Law - Ali, Younis (Journal of Legal Sciences, 2023)
The Gift is considered as a legal voluntary non-contractual transaction or disposition to transfer the granted property from the donor to donee  gratuitously or without consideration. It is also worth-bearing in mind that the want of the requirement of consideration is the reason that the gift is not classified within the scope of the contract. And it is normally classified into two types: The inter vivos gift  and gift causa mortis. It should also be noted that the donatio (or gift) inter vivos is applied to both the personal property or chattels and real property equally. As opposed to the gift causa mortis, which is applied to the personal property or chattels rather than the real property. Whereas both the Iraqi Civil Law No. (40) of 1951, regulated the gift and considered it as a nominate contract, concluded with or without gratuity. And generate a lot of obligations.